Autism and the right to education in the EU: Policy mapping and scoping review of the United Kingdom, France, Poland and Spain. - Monika Roleska; Andres Roman-Urrestarazu; Sarah Griffiths; Amber N V Ruigrok; Rosemary Holt; Robin van Kessel; Kathleen McColl; William Sherlaw; Carol Brayne; Kasia Czabanowska (PLoS ONE)
Introduction Autistic people may have different educational needs that need to be met to allow them to develop their full potential. Education and disability policies remain within the competence of EU Member States, with current educational standards and provisions for autistic people implemented locally. This scoping review aims to map EU and national special education policies with the goal of scoping the level of fulfilment of the right to education of autistic people. Methods Four EU countries (United Kingdom, France, Poland and Spain) were included in this scoping review study. Governmental policies in the field of education, special education needs and disability law were included. Path dependency framework was used for data analysis; a net of inter-dependencies between international, EU and national policies was created. Results and discussion Each country created policies where the right to free education without discrimination is provided. Poland does not have an autism specific strategy, whereas the United Kingdom, France and Spain have policies specifically designed for autistic individuals. Within the United Kingdom, all countries created different autism plans, nevertheless all aim to reach the same goal-inclusive education for autistic children that leads to the development of their full potential. Conclusion Policy-making across Europe in the field of education has been changing through the years in favour of autistic people. Today their rights are noticed and considered, but there is still room for improvement. Results showed that approaches and policies vastly differ between countries, more Member States should be analysed in a similar manner to gain a broader and clearer view with a special focus on disability rights in Central and Eastern Europe.